Dari Besuki ke Bondowoso: Perkembangan kawasan frontier terakhir di Jawa 1800-1930 - Jati Saputra Nuriansyah; Intan Aninditya; Moh. Yopi Putra Ramadhani; Hastrida Firdaus Iva; Rizqy Syahrul Romadhon (Historiography: Journal of Indonesian History and Education, 2022)
This article describes the development of the Besuki residency as the last frontier area on the island of Java for the period 1800-1930. This writing is motivated by the development of government and the socio-economic life of the people in the Besuki Residency area. The methods used in this study include heuristics, verification, interpretation, and historiography. The purposes of writing this article are 1) To find out the development of government in Besuki Residency; 2) To describe the economic development in Besuki Residency; and 3) To describe the social conditions of the Besuki Residency community.Dalam artikel ini memuat tentang perkembangan Karesidenan Besuki sebagai wilayah frontier terakhir di Pulau Jawa periode 1800-1930. Penulisan ini dilatar belakangi oleh perkembangan pemerintahan dan kehidupan sosial ekonomi masyarakat di wilayah Karesidenan Besuki. Metode yang digunakan dalam penelitian ini meliputi heuristik, verifikasi, interpretasi, dan historiografi. Adapun tujuan dari penulisan artikel ini yaitu 1) Untuk mengetahui perkembangan pemerintahan di Karesidenan Besuki; 2) Untuk mendeskripsikan perkembangan ekonomi di Karesidenan Besuki; dan 3) Untuk menjabarkan keadaan sosial masyarakat Karesidenan Besuki.